Second-best carbon taxation in the global economy: the Green Paradox and carbon leakage revisited - van der Ploeg, F (Elsevier, 2016)
Acceleration of global warming resulting from a future carbon tax is large if the price elasticities of oil demand are large and that of oil supply is small. The fall in the world interest rate weakens this weak Green Paradox effect, especially if intertemporal substitution is weak. Still, social damages from greenhouse gases drop if the fall in oil supply and cumulative emissions is strong enough. If the current carbon tax is set too low, the second-best future carbon tax is set below the first best too to mitigate adverse Green Paradox effects. Unilateral second-best optimal carbon taxes exceed the first-best taxes due to an import tariff component. The intertemporal terms of trade effects of the future carbon tax increase current and future tariffs and those of the current tax lower the current tariff. Finally, carbon leakage and globally altruistic and unilateral second-best optimal carbon taxes if non-Kyoto oil importers price carbon too low are analysed in a three-country model of the global economy.